Recovery and Purification of Protein Aggregates From Cell Lysates Using Ceramic Membranes: Fouling Analysis and Modeling of Ultrafiltration - Birrenbach, Oliver; Faust, Frederik; Ebrahimi, Mehrdad; Fan, Rong; Czermak, Peter (Frontiers in Chemical Engineering, 2021)
The characterization of membrane fouling provides valuable information about the performance and operational range of filtration processes. The range of operational parameters for the purification and concentration of protein aggregates from cell lysates by ultrafiltration is determined by evaluating the filtration resistances. We therefore investigated the cross-flow ultrafiltration of ovalbumin aggregates with a mean size of 304 nm using a 50 nm cut-off ceramic membrane. We observed a 90% decline in flux within the first 10 min of filtration, demanding an in-depth analysis of membrane fouling. Resistance-in-series analysis revealed that the main filtration resistance originated from the cell lysate in the feed solution. Flux decline was monitored at different transmembrane pressures and concentrations for the most significant fouling phenomenon, indicating that the intermediate pore blocking model correlated best with the observed filtration data. The transmembrane pressure for purification and concentration was set at 1.5 bar based on the prediction of a limited, mostly pressure-independent flux of 12 L·m 2·h 1 for solutions with an ovalbumin aggregate concentration of 0.5 g·L-1. Higher pressure increased the filtration performance only slightly, but led to a linear increase in filtration resistance. A 10-fold variation in protein aggregate concentration strongly influenced filtration performance, with higher protein concentrations increasing the filtration resistance by 413% and causing an 85% decline in flux.